Mariategui: Perspectives from the symbolic conception of Nation History in formation-Nation formed and “Though - Castillo Ochoa, Manuel (2020)
This work investigates, from the approach of materialist conception of history (MCH) about one the classics Latin American and Peruvian debates, the one of the nations in formation or formed nation. This paper is based on the discussion that arose between J.C. Mariátegui and the Argentine Palacios, in the decade of 20ths in Latin America about whether or not the exitance of Latin American thoughts, and relocates  the discussion in the light of new theoretical turns recently occurred, and  progress on the proposal from Mariátegui against Palacios highlighting the “Hermeneutic” of Mariátegui. It also includes a debate that took place in the middle of the first decade of the present century, but according to the author, it  did not give due importance to the “mentality” and “thought” that Mariátegui emphasized in front of Palacios to deal with the national formation subject, and without leaving aside the material specificity of Peruvian National formation. In addition, it also stands out other national authors who have addressed the subject.